From detection to sentencing: a homicide case flow analysis of the Dutch criminal justice system - Liem, Marieke (Policing and society, 2022)
Homicide engenders broad moral concerns in society, and its aftermath can be understood as a barometer for criminal justice policy. Of all homicides committed, however, only some lead to arrest, to prosecution and ultimately to conviction in court. So far, no study has assessed the entire flow of homicide cases through the criminal justice system based on a nationwide sample. This study seeks to fill this empirical void by describing the entire flow of homicide cases and assessing the size of outflow at each stage of the criminal justice funnel in the Netherlands for a 20-year period. Our analysis highlights two main findings: First, the vast majority of suspects first identified by the police are ultimately sentenced for a homicide. Second, even in a country with low homicide rates and high rule of law indices, selection takes place at all stages of the criminal justice funnel. Whilst outflow mostly centres around exceptional clearance and legal factors, future work should assess the extent to which extra-legal characteristics play a role in crimes that are being investigated as potential homicides.